Eksistensi Bimbingan Perkawinan Pranikah di Wilayah Kecamatan Ujung Tanah Kota Makassar - Ahmad Jazil (Al-Mizan (e-Journal), 2020)
Pre-marital marriage cource aims to equip brides-to-be with understanding and knowledge and skills about married life, hoping that in the future they can create a harmonious family while reducing conflict, domestic violence and divorce. This study discusses the existence of pre-marital marriage course in the Ujung Tanah District, Makassar City. This study uses a qualitative approach with data collection methods through interviews. The results of this study indicate that participants of premarital marriage course in the Ujung Tanah District, Makassar city are participants who have registered at the Office of Religious Affairs, but have not yet entered into a marriage contract. The fact that after following pre-marital marriage course, the couples feel each other's self confidence increases and their are better prepared to live a domestic life, so that the existence of pre-marital marriage course can create a happy family. However, in the implementation there were also obstacles faced by the facilitators and the guidance participants.